Design and performance analysis of stand-alone PV system at Al-Nahrain University, Baghdad, Iraq - Anas Lateef Mahmood; Amina Mahmood Shakir; Bahaa Abdulkhaliq Numan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The use of the stand-alone PV systems for electric power generation is important to meet the needs of electric power, especially in countries that have major problems in the generation and continuity of electricity such as Iraq. The aim of this research is to design and simulate a stand-alone PV system installed on the roof of the parking garage in the College of Engineering at Al-Nahrain University for the purpose of using the electrical energy generated by this system to meet the energy demand of the daily light for the parking garage and engineering laboratories buildings beside it. The main factor in the design was the total area of the roof of the parking garage. The Pvsyst6 program is used to simulate the suggested PV system and to determine the effect of partial shading which caused by the trees surrounding the garage on the available generated power of the system. A comparison was made between four types of solar panels to see the suitability of these types to the weather conditions in Iraq, in addition to the impact of the shadows surrounding the garage. These types of solar panels were (CIS SL2-145, CdTe F-4112-3, Poly JAP6-60-260, and Mono JAM6-60-260), CdTe type showed better performance compared to other types in terms of available energy generated because it has small losses due to temperature and shadows. It was found that the best tilt angle of the solar panels in the case of shadows is 19o to the south. Finally, the financial analysis was made to see the economic feasibility of this PV system and it is found that the PV system that uses CdTe panels has the smallest kWh unit price (0.236 $/kWh) as compared with the other three types.